Geochemical Characteristics of Formation Water in Carbonate Reservoirs and Its Indication to Hydrocarbon Accumulation. (11th October 2022) - Sun, Zhen; Yang, Zhen; He, Xiaoning; Wan, Cixuan; He, Gang; Ren, Qiang; Zhao, Shihu; Cheng, Wei; Chen, Sisi
Abstract : The migration path of formation water plays an indispensable role in hydrocarbon accumulation and preservation. The hydrodynamic field controls the content of various ions in formation water and is an important participant in hydrocarbon evolution. Formation water can basically be used to judge the preservation status of oil/gas reservoirs, especially for carbonate reservoirs; the carbonate reservoirs are a typical example in the Gaoqiao area of the Ordos Basin, China. However, it is not easy to evaluate the sealing and integrity of the gas reservoir because hydrocarbon has experienced a multistage charging process and complicated later reconstruction. The geochemical characteristics of Ordovician formation water (100 brine samples from 67 wells in the Ma5 Member) are studied, and their chemical composition is analyzed in the Ordos Basin. The results show that formation water has high overall salinity and is the original sedimentary water of the carbonate reservoir, which is the sealing reservoir and can promote the accumulation of hydrocarbons. This is also associated with stronger water-rock reactions and diagenetic transformations, such as dolomitization. The main (TDS) range is from 40 to 150 g·L −1, with an average of 66.16 g·L −1 ; the Cl − content in the formation water samples is the highest, followed by Ca 2+, Na +, Mg 2+, HCO3 −, and SO4 2− . In addition, the (Cl − -Na + )/Mg 2+ ratio, Na + /Cl − ratio, Mg 2+ /Ca 2+ ratio, and S O 4 2 − × 100 / C l − ratio are closely related to gas preservation. The indication function between chemical parameters of formation water and hydrocarbon dynamics can be better understood in carbonate reservoirs by analogy study, so as to improve the accuracy of discriminating favorable hydrocarbon accumulation areas.